A Scoping Review of Registered Clinical Studies on Management of Individuals With Acute Spinal Cord Injury (2000–2020): Trends and Characteristics of the Research Initiatives. (February 2022) - Furlan, Julio C.; Furlan, Daniel T.; Marquez-Chin, Cesar
Abstract : Abstract: This scoping review examined the current trends and characteristics of the clinical research initiatives on the management of acute spinal cord injury. This review included all clinical studies on the acute treatment of spinal cord injury that were registered in the ClinicalTrials.gov website from February 2000 to December 2020. The search strategy combined the terms "acute spinal cord injury" and "treatment." There has been a gradual increase in the number of registered clinical studies on acute treatment of spinal cord injury over the past two decades. Of the 116 studies, there were 103 interventional studies, 12 observational studies, and 1 registry. While 115 clinical studies recruited male and female participants, most of the registered clinical studies included only adults with an upper age limit after spinal cord injury. Most of the registered clinical studies were interventional studies led by single institutions in North America ( n = 70), Europe ( n = 29), and Asia ( n = 15). Most of the research initiatives were interventional studies on new therapies for management of individuals with spinal cord injury ( n = 91). In conclusion, the results of this scoping review suggest that although there has been an increase in the amount and diversity of the research initiatives on treatment of acute spinal cord injury over the past two decades, their generalizability remains relatively limited.